Collaborative mobile instant messaging learning pedagogical model for teacher training / Khairah @ Asma’a Baharun - Khairah @ Asma’a , Baharun (2018)
Mobile Instant Messaging (MIM) is one of a social media application that is increasingly being viewed as a tool to enhance learning delivery in the mobile learning environment. Its potential to support collaborative learning has gain interest in education because of its compelling features such as speed, interactivity and less cost. Therefore, this study was conducted to develop a Collaborative Mobile Instant Messaging Learning (CMIML) pedagogical model for teacher training. The study adopted the Design and Development Research (DDR) approach. Based on the approach, the study was conducted in three phases. The first phase is the Needs Analysis phase that aimed to identify a need to develop the CMIML pedagogical model for teacher training. This survey was based on lecturers‟ perceptions and level of acceptance and intention to use CMIML if incorporated in the formal course. This study involved 268 lecturers in Malaysia Institute of Teacher Education. The instrument used for this phase is a set of need analysis survey questionnaire which is constructed based on Unified Theory of Acceptance and Use of Technology (UTAUT). The second phase of the study is the design and development stage which adopted Nominal Group Technique (NGT) and Interpretive Structural Modelling (ISM) techniques in order to develop the CMIML Pedagogical Model for teacher training. The findings of the study constitute the result of the experts‟ collective views on the pedagogical activities and the relationships among the activities. The final phase of this study is to evaluate the CMIML Pedagogical model. This phase is to determine the suitability of the model as support to formal learning for teacher training. This evaluation phase has applied a modified Fuzzy Delphi Method (FDM) to determine the consensus‟ views and opinions from 25 selected panel of experts based on their responses to a five-linguistic scale survey questionnaire. The „threshold‟ value „d‟ was calculated to determine the experts‟ consensus for all questionnaire items while the defuzzification (Amax) values for the items would determine the agreement of the experts. The findings for Phase 1 indicated the need for the study to develop the model. Findings from Phase 2 resulted in the development of the model that consisted of 27 pedagogical activities determined by a panel of experts. From the model developed, the experts viewed that the pedagogical activities could be divided into five categories and four activity clusters to facilitate the interpretation of the roles of the activities. Finally, findings from Phase 3 showed that all the items have met the requirements needed in the triangular fuzzy number and deffuzification process which revealed that all experts consensually agreed with these questionnaire items. The result of the study can be useful to policy makers, lectures and instructors as it provides guidelines and considerations required in conducting mobile learning. Thus, the pedagogical model is expected to improve the delivery of teaching and learning methods to be more efficient through planning in shaping the framework of the course better.